Theoretical solvent selection for nanostructured surface fabrication of reusable and colourimetric visual-eye sensor strips with rhodamine derivative-encapsulated polymeric membranes for highly sensitive and selective detection of Hg2+. (May 2021) - Girdthep, Sutinee; Hanmeng, Oranual; Triamnak, Narit; Chailek, Nirumon; Wanichacheva, Nantanit
Abstract: Homogenous electrospinnable solutions were prepared through theoretical solvent selection using the high solubility parameters of rhodamine derivatives (rhodamine B hydrazide, RBH and rhodamine 6G hydrazide, R6GH) and poly(methylmethacrylate) (PMMA). Results of the systematic method showed that the best solvent for the Hg 2+ -sensing membranes was ethanol/tetrahydrofuran at 0.6/0.4 (v/v). PMMA/RBH and PMMA/R6GH membranes were fabricated using electrospinning. The optimal PMMA concentration was 11 wt%. The PMMA/RBH and PMMA/R6GH membranes possessed a nanostructured smooth surface with a high surface area of ultra-fine narrow nanofibres (about 2.5 μm in diameter). Given their high surface area with narrow-diameter fibres, the PMMA/RBH and PMMA/R6GH electrospun membranes showed high selectivity and sensitivity fluorescent sensing of Hg 2+ ion with low detection limit (ranges of 0.8–1.099 and 3.6–4.3 ppb, respectively) than the sensor-encapsulated polymeric membranes prepared by spinning technique. The sensing membranes provided a vibrant colourimetric response unique to Hg 2+ ions (white-pink) over other potential interfering metal cations that were observed within 30 s by the visual eye. Furthermore, the membranes were effective for reuse up to four times with a high fluorescence intensity. Therefore, PMMA/RBH and PMMA/R6GH can be used as portable colourimetric visual-eye and fluorescent sensors for the easy real-time monitoring of Hg 2+ ions in dietary and environment sources. Highlights: Theoretical selection reduced time to investigate the best solvent for nanostructured surface of membranes fabrication. Membranes were a sufficient selective and sensitive to detect the maximum-allowed Hg 2+ contamination in drinking water. Colorimetric visual-eye and fluorescent sensor of PMMA/RBH and PMMA/R6GH membranes are reusable.